Survey of Alternaria leaf blight incited by Alternaria alternata for dissease severity under different Isabgol growing agro-climatic regions - Abhishek Katiyar; Ram Suman Mishra; Anand Milan; Deepak Singh; Shivam Kumar; Uma Shankar; Harshit Gupta (The Bioscan, 2026)
A roving survey was conducted during the Rabi seasons 2023–24 and 2024–25 to assess the geographic variation in disease severity of Alternaria blight caused by Alternaria alternata across twenty locations representing diverse agro-climatic regions. Survey revealed a wide range of disease severity, with the average per cent disease severity (PDS) varying from 2.15 to 16.11 per cent, indicating considerable spatial variability in disease severity. This disease was prevalent in all surveyed locations, confirming the widespread distribution of the pathogen. The highest disease severity was recorded at Jinjinyala, Jodhpur, Rajasthan (16.11%), which was statistically at par with Medicinal and Aromatic Plant Garden, Anand, Gujarat (14.95%) and BRC Farm, Jodhpur (14.52%). A moderately high disease severity group comprised Menar F-1, Udaipur (13.47%), Khambolaz village, Anand (12.54%), ARS Farm, Mondor (12.23%), Kalakh, Jobner (12.20%), and Main Experimental Farm, Hisar (12.13%), which were statistically comparable, indicating similar epidemiological conditions favorable for disease development. Moderate disease severity was observed at Kunjrao village, Anand (11.65%), Manpuriya F-1, Mandsaur (11.37%), RCA Farm, Udaipur (11.32%), and Ranchhodpura village, Anand (11.23%), while lower disease intensity was recorded at Baori, Nagaur (9.88%), ANDUAT, Ayodhya (9.74%), MAPB at NRC on Seed Spices, Ajmer (8.80%), RVSKVV, Mandsaur (8.30%), and KVK Tabiji Farm, Ajmer (7.98%). The minimum disease severity was observed at Haripura, Jaipur (5.56%), Bhainslana, Jobner (4.26%), and Bhookhronki Dhani, Jobner (2.15%). Keywords Isabgol, Plantago ovata, Alternaria blight, Alternaria alternata, disease severity, roving survey, agro-climatic variability, epidemiology